Influence of enhanced electrogenicity on anodic biofilm and bioelectricity production by a novel microbial consortium. (May 2021) - Ajunwa, Obinna Markraphael; Odeniyi, Olubusola Ayoola; Garuba, Emmanuel Oluwaseun; Marsili, Enrico; Onilude, Abiodun Anthony
Graphical abstract: Highlights: Pseudomonads, Bacillus sp., Enterobacter sp. and Pichia sp. made up the consortium. Electrode pretreatment and metabolic enhancers improved consortium electrogenicity. Improved biofilm production was achieved using a metabolically enhanced consortium. Metabolic enhancement is a promising technique in bioelectricity generation. Abstract: Biofilms, flavins and pyocyanin have been identified as metabolites for species-specific electrogenicity. In this work, open circuit voltages (OCV) >500 mV earlier produced by electrogens in glucose-based media was used in confirming electrogens. Biofilms of test electrogens were grown on anodes of microbial fuel cells (MFCs) fed with glucose-based media. Electrogens used were anodophilic Enterobacter aerogenes 102, flavinogenic Bacillus sp. 101, Pichia kudriavzevii 103 and four pyocyanogenic Pseudomonads. Treatments with inhibitors (norspermidine, dichloro-diaminobenzene, and Raloxifene) negatively affected their electrogenicity. To enhance electrogenicity, increased anodic-biofilm was achieved by anode pretreatments with ultraviolet radiation and hydrogen peroxide, while pyocyanin-induced electrogenicity was enhanced by treatment with sophorolipds. Improved flavin yield and electrogenicity production was achieved by treatment with dimethyl-diaminobenzene. Bioelectricity production using metabolically-enhanced electrogens was carried out in a modified MFC and optimum yields were achieved using a consortium of all electrogens exposed to metabolic enhancements. Measurements of electrochemical potential showed improved electrogenicity in metabolically-enhanced consortium compared to the unenhanced consortium. Using eight MFCs in series, OCV value of 5000 mV was achieved, while parallel connections yielded increased current up to 6000 mA/m 2 . Electron microscopy showed well-developed biofilms formed by metabolically-enhanced consortium. EPS from consortium biofilm were also characterized using fourier transform-infrared (FT-IR) spectroscopy.